Late onset psychosis in a case of 15q11.2 BP1-BP2 microdeletion () syndrome: A case report and literature review - Soumitra Das; Vallabh Shet; Sanjana Palakodeti; Prakriti Pokhrel; Maliha Ansari; Osama Qutaish; Mukund Rao; Shyam Ravilla (SAGE Open Medical Case Reports, 2024)
Burnside–Butler syndrome is an inheritable genetic condition characterized by the partial deletion of specific genetic material located on chromosome 15q11. Individuals diagnosed with this particular medical condition display a variety of neuropsychiatric disorders, including psychosis, aggression, mood disorders, anxiety disorders, developmental disorders involving learning difficulties, language delays, autism spectrum disorders, and attention-deficit/hyperactivity disorder. The authors discuss the case of a 51-year-old Caucasian female diagnosed with Burnside–Butler syndrome at 8 years. The article highlights the importance of raising awareness regarding the complex nature and delayed onset of neuropsychiatric symptoms associated with this syndrome. It also emphasizes the need for comprehensive evaluation and multidisciplinary care for individuals affected by this uncommon condition.